Timing and Outcome of Endovascular Repair for Uncomplicated Type B Aortic Dissection. (May 2021) - Xie, Enmin; Yang, Fan; Liu, Yuan; Xue, Ling; Fan, Ruixin; Xie, Nianjin; Chen, Lyufan; Liu, Jitao; Luo, Jianfang
Abstract : Objective: This study aimed to determine the effect of intervention timing, from symptom onset to thoracic endovascular aortic repair (TEVAR), on early and late outcomes in high risk patients with uncomplicated type B aortic dissection (uTBAD). Methods: The study retrospectively evaluated 267 uTBAD patients with high risk radiographic features who underwent pre-emptive TEVAR during the acute and subacute periods. Demographics, comorbidities, pre-operative imaging features, peri-procedural details, and follow up outcomes were analysed. Results: Among the 267 pre-emptive TEVARs for high risk uTBAD, 130 were performed in the acute phase (1–14 days); and 137 in the subacute phase (15–90 days), from initial presentation. The mean age was 55.9 ± 11.0 years and 222 (83.1%) were men. The 30 day mortality rate in the acute group was five times higher than that in the subacute group (3.8% vs. 0.7%), although without statistically significant difference ( p  = .11). No statistically significant difference in 30 day outcomes (aortic rupture, retrograde type A dissection [RTAD], immediate type Ia endoleak, stroke, spinal cord ischaemia, and re-intervention) was noted ( p > .05 for each). Of note, aortic rupture, RTAD, and disabling stroke were observed only in the acute group. Multivariable logistic analyses showed that intervention timing was not associated with 30 day outcomes. The median clinical follow up was 48.2 ± 25.9 months (range 1 – 106 months). There were no significant differences in all cause mortality, dissection related death, late intervention, or aortic related late events among timing cohorts ( p > .05 for each). Furthermore, aortic remodelling, by analysing the flow status of the false lumen and evaluation of aortic diameters, either at the thoracic aorta level or the abdominal aorta level, was similar between the two groups. Multivariable Cox analyses showed that intervention timing was not associated with late outcomes. Conclusion: The present study indicates that TEVAR for high risk uTBAD in the acute phase was associated with a trend toward higher rates of early complications, while the long term outcomes were comparable with those of the subacute phase.